Kajian Komparatif Buku Pop-Up Fiksi untuk Dewasa - Salwaa Davasha Gita Aulia Ratna; Wuri Widyani Hapsari (CITRAKARA, 2026)
Pop-up books are conventionally identified as literacy media for children. However, contemporary developments in visual communication design have opened wide opportunities for exploration targeting adult audiences who require more complex, deep, and immersive narrative experiences. This study aims to compare the design strategies of adult fiction pop-up books through two distinct approaches: a focus on world-building in the case study of Game of Thrones, and a focus on character-driven narrative in the case study of Bram Stoker's Dracula. The research method employed is descriptive qualitative, utilizing literature studies, mechanical structure observation of paper engineering techniques, and perception surveys to map the aesthetic preferences and emotional responses of adult audiences. The results indicate that both approaches require significantly different mechanical manifestations. In Game of Thrones, macro-scale paper engineering mechanisms, such as parallelogram structures and multi-tiered folds, are effectively utilized to construct spatial grandeur, architectural complexity, and physical landscapes of the fictional world. Conversely, in Bram Stoker's Dracula, micro-interactive mechanisms such as pull-tabs, volvelles, and hidden form transformations are applied to subtly visualize psychological changes, a horror atmosphere, and the emotional depth of the characters. The conclusion of this study emphasizes that the effectiveness of adult fiction pop-up books highly depends on the precise synchronization between paper engineering techniques and the core narrative pillars. The world-building approach demands vast and grand spatial representations, whereas character narrative requires more intimate and personal physical interactions to reinforce textual interpretation. Thus, pop-up books are proven to be an exploratory medium in visual communication design capable of dynamically combining engineering art, literary narrative, and tactile interaction for adult readers.